Carbon Footprint of Milk Processing—Case Study of Polish Dairy - Magdalena Wróbel-Jędrzejewska; Anna M. Klepacka; Ewelina Włodarczyk; Łukasz Przybysz (Agriculture)
Sustainable milk processing is essential to minimize negative environmental impacts. The purpose of this study was to determine the carbon footprint (CF) of the production of milk products in an industrial plant in Poland. Annual production and technological processes were analyzed, and relevant parameters were determined, as well as the method of data collection according to the chosen method of analysis and the developed database. It was found that each process is a source of greenhouse gas (GHG) emissions and affects the CF of the product. The total carbon footprint of the production of milk products was 0.367 kgCO2eq/kg. The average GHG emissions associated with production came mainly from indirect emissions (electricity consumption) and accounted for 50% of the total emissions. The determined relationship between the CF and monthly production volume also allows production planning in the context of sustainability. An increase in the monthly production volume by about 12% results in a reduction in the carbon footprint by about 18%. Decarbonization of dairies is possible through the use of renewable energy sources. Determining the CF of milk processing is the first step toward reducing GHG emissions, improving the sustainability of the sector and aligning with global trends and regulations.